Postweaning Iron Deficiency in Male Rats Leads to Long-Term Hyperactivity and Decreased Reelin Gene Expression in the Nucleus Accumbens. Issue 2 (10th October 2019) - Nishikura, Noriko; Hino, Kodai; Kimura, Tomoko; Uchimura, Yasuhiro; Hino, Shinjiro; Nakao, Mitsuyoshi; Maruo, Yoshihiro; Udagawa, Jun
ABSTRACT: Background: Epidemiological research indicates that iron deficiency (ID) in infancy correlates with long-term cognitive impairment and behavioral disturbances, despite therapy. However, the mechanisms underlying these effects are unknown. Objective: We investigated how ID affected postweaning behavior and monoamine concentration in rat brains to determine whether ID during the juvenile period affected gene expression and synapse formation in the prefrontal cortex (PFC) and nucleus accumbens (NAcc). Methods: Fischer 344/Jcl postweaning male rats aged 21–39 d were fed low-iron diets (0.35 mg/kg iron; ID group) or standard AIN-93 G diets [3.5 mg/kg iron; control (CN) group]. After day 39, all rats were fed the iron-adequate diet. The locomotor activity was evaluated by the open field and elevated plus maze tests at 8 and 12 wk of age. Monoamine concentrations in the brain were analyzed using HPLC at 9 and 13 wk of age. Comprehensive gene expression analysis was performed in the PFC and NAcc at 13 wk of age. Finally, we investigated synaptic density in the PFC and NAcc by synaptophysin immunostaining. Results: Behavioral tests revealed a significant reduction of the age-related decline in the total distance traveled in ID rats compared with CN rats ( P < 0.05), indicating that ID affected hyperactivity, which persisted into adulthood (13 wk of age). At this age, reelin ( Reln ) mRNA expression (adjusted P < 0.01) decreased and synaptic density ( P < 0.01) increased in the NAcc in the ID group. Regarding the mesolimbic pathway, homovanillic acid concentration increased in the NAcc, whereas the dopamine concentration decreased in the ventral midbrain. Conclusions: Our results suggest that ID during the postweaning period in male rats, despite complete iron repletion following ID, led to long-term hyperactivity via monoamine disturbance in the brain and an alteration in the synaptic plasticity accompanied by downregulation of Reln expression in the NAcc.